Undergraduate nursing students' knowledge and experience in infusion therapy and peripheral vascular acces - Jaciara Tiago Antunes Alvarenga; Adriana Cristina Nicolussi; Aline Maria Pereira Cruz Ramos; Lucas Fernando Antunes Gomes; Damiana Aparecida Trindade Monteiro; Silmara Elaine Malaguti Toffano (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the knowledge and experience of undergraduate nursing students regarding infusion therapy and peripheral vascular access. Methods: descriptive, cross-sectional, analytical study with 123 undergraduate nursing students who answered a semi-structured instrument. Results: the majority were women, with a median age of 51 years old; 87% considered the teaching received insufficient to perform in clinical practice. The mean overall knowledge score was 78.1 (SD± 8.97). The themes catheter flushing and lock (38.1%), catheter selection (34.2%), infusion equipment (30.9%) and insertion site (30.9%) presented a significant number of errors. Conclusions: practical classes and execution of procedures in health services were predictors for a better knowledge about infusion therapy and vascular access by undergraduate nursing students.